2018
DOI: 10.1159/000490548
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Prognosis of Nontuberculous Mycobacterial Pleuritis

Abstract: Background: While nontuberculous mycobacterial (NTM) pleuritis rarely complicates pulmonary NTM infection, high mortality has been reported in case reports and small studies. Objectives: The purpose of this study was to clarify the clinical features and treatment outcomes of pulmonary NTM infection cases accompanied by NTM pleuritis. Methods: Medical records of 1,044 patients with pulmonary NTM disease were retrospectively reviewed to select patients complicated by NTM-proven pleuritis. We investigated clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 29 publications
2
31
1
Order By: Relevance
“…Korea reported that 1.2% of patients from whom NTM had been isolated from sputum had confirmed or suspected NTM pleuritis. Ichiki et al (21) reported that the frequency of PE in patients with pulmonary NTM was 3.4%, Takahiro Ando et al (8) reported that the frequency of PE in patients with pulmonary NTM was 1.4%. In our report, 7% of cases with NTM diseases developed pleuritis with NTM isolated from PE.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Korea reported that 1.2% of patients from whom NTM had been isolated from sputum had confirmed or suspected NTM pleuritis. Ichiki et al (21) reported that the frequency of PE in patients with pulmonary NTM was 3.4%, Takahiro Ando et al (8) reported that the frequency of PE in patients with pulmonary NTM was 1.4%. In our report, 7% of cases with NTM diseases developed pleuritis with NTM isolated from PE.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Therefore, the prevalence of NTM pleurisy has become a clinical concern. Moreover, it was reported that the presence of pleural effusion (PE) in NTM patients was considered as an adverse prognostic factor (8)(9)(10). Until now, few studies were performed to evaluate the clinical-pathological characteristics, treatment and prognosis of NTM pleurisy.…”
Section: Introductionmentioning
confidence: 99%
“…Ando et al reported 15 cases (1.4%) of NTM pleuritis among 1044 patients with NTM lung disease. [ 6 ] Park et al demonstrated 14 patients with NTM pleuritis in a 17-year retrospective study of the data of a single tertiary hospital. [ 7 ] Naito et al and Yoon et al reported retrospective data of 12 patients over 15 years and 5 patients over 13 years in a single center each.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, primary NTM pleurisy (i.e., without distinct pulmonary involvement) is rare, probably because NTM are environmental mycobacteria inducing desensitization in hosts before its infection (53). NTM pleurisy may be caused by a direct extension of infection from pulmonary lesions into the pleural cavity and is often intractable (54)(55)(56). Endoscopic examination to diagnose PNTMD was reported to cause NTM pleuritis with pneumothorax probably due to the rupture of a subpleural lesion during the procedure (20, 57).…”
Section: Pleurisymentioning
confidence: 99%